Advancements in the investigation of radioactive microspheres for brachytherapy - Jiang, Xiaohui; Chen, Lei; Xu, Xiao (Frontiers in Bioengineering and Biotechnology, 2025)
In clinical practice, the management of most non-surgically resectable solid tumors necessitates a multidisciplinary treatment approach. Optimal solutions involve the integration of local and systemic treatments, such as targeted immunotherapy and chemotherapy. Micron-sized radioactive microspheres or particles have gained widespread application in the localized treatment of various organ tumors, encompassing liver cancer, lung cancer, tongue cancer, pancreatic cancer, head and neck cancer, ovarian cancer, bone cancer, among others. As such, the design and development of novel multifunctional radioactive microspheres constitute a crucial foundation for achieving effective local treatment in liver cancer and other cancer types. This article critically reviews the current developmental landscape, identifies challenges, and explores opportunities in the field of radioactive internal irradiation microspheres in recent years. The insights provided serve as a valuable reference for selecting and determining the developmental direction of clinical brachytherapy treatment carriers.